The Design of E-Learning (share.its.ac.id) Course “Sistem Pengendalian Otomatis” to Support Effective Learning Outcomes - Syamsul Arifin; Aulia Siti Aisjah; Nurlita Gamayanti; Tutug Dhanardono; Yaumar Yaumar; Yusuf Bilfaqih (IPTEK Journal of Proceedings Series, 2015)
Open and integrated online learning is learning that promotes the use of learning content from colleges that have more resources for other universities in Indonesia. Subjects – “Sistem Pengendalian Otomatis” (SPO) 4 credits, one of subject in Engineering Physics Department, has been tested for blended learning with partner universities, between ITS with ITN Malang, ITT Bandung. Currently e-learning use by Sriwijaya University, UNSRAT-Menado and MUSAMUS-Merauke. Learning object designed in 8 Sub Achievement Learning - SCP, in cognitive, psychomotor and affective, in the activities: independent study, groups study in guided by lecturer, synchronous and asynchronous learning. Affective abilities measured by activity chats, forums, management capabilities to upload time of task, and the ability of communicate in writing. Psychomotor ability is measured by skill in the design of control in the mini plant or object and skill in programming. The skill have recorded by video camera and uploaded in the share.its.ac.id. Student followers of SPO course showed cognitive abilities, and 92% of them have met the achievement standards that have been set.